Multiplexed functionalization of nanoelectromechanical systems with photopatterned molecularly imprinted polymers. (14th January 2019) - Dezest, D; Leïchlé, T; Teerapanich, P; Mathieu, F; Bui, B Tse Sum; Haupt, K; Nicu, L
Abstract: Implementing dedicated and reliable biochemical recognition functionalities onto nanoelectromechanical systems (NEMS) is of primary importance for their development as ultra-sensitive and highly-integrated biosensing devices. In this paper, we demonstrate the large-scale and multiplexed integration of molecularly imprinted polymers (MIPs) as highly stable biomimetic receptors onto arrays of nanocantilevers. Integration is carried out by spin-coating and photopatterning the polymer layers before releasing the nanostructures. We demonstrate that these biomimetic layers are robust enough to withstand the wet-etch of the sacrificial layer making this functionalization strategy compatible with further MEMS/NEMS processing. As a proof of concept, we fabricate NEMS resonators coated with a MIP using Boc-L-phenylalanine as the template molecule. We demonstrate the preserved molecular recognition ability of the patterned sensitive layer through the fluorescence detection of dansyl-L-phenylalanine, a fluorescent derivative of the template, and the mechanical integrity of the resonators by means of resonant frequency measurements.